Personal, Social, and Lifestyle Factors Influencing Male Purchase Intentions in Beauty Clinics - Tuminah; Audita Nuvriasari (LifeSciFi, 2025)
In recent years, an increasing awareness of appearance among men has led to a rise in their interest in beauty clinic services. This shift underscores the importance of understanding the factors that influence male consumers’ purchase intentions in this industry. This study aims to analyze the influence of personal factors, social media marketing, and lifestyle on male consumers ‘purchase intentions for beauty clinic services. This study used a quantitative approach with a purposive sampling technique, involving 100 male respondents who completed a distributed questionnaire. Instrument testing confirmed the validity and reliability of the data. Furthermore, classical assumption tests indicated that the data were normally distributed and the regression model was free from multicollinearity and heteroscedasticity. The results showed that all three independent variables had a significant and positive influence on the purchase intentions of male consumers. Specifically, personal factors, social media marketing, and lifestyle were found to have a significant influence on the decision to use beauty clinic services. In conclusion, these findings underscore the importance of considering these three aspects when targeting male consumers in the beauty sector, particularly to refine marketing strategies and enhance customer engagement in urban areas.